Ancient fiction: the matrix of early Christian and Jewish narrative - Brant, Jo-Ann A.; Hedrick, Charles W.; Shea, Christine Rita (Symposium series, 2005)
The educational curriculum in Chariton's Callirhoe / Ronald F. Hock -- Imitating imitation : Vergil, Homer, and Acts 10:1-11:18 / Chris Shea -- Die Entführung in das Serail : Aspasia : a female Aesop? / Richard I. Pervo -- Novel and mystery : discourse, myth, and society / Gerhard van den Heever -- Midrash as fiction and midrash as history : what did the rabbis mean? / Chaim Milikowsky -- Mimesis and dramatic art in Ezekiel : the tragedians' exagoge / Jo-Ann A. Brant -- Daniel 1-6 : a biblical story-collection / Tawny L. Holm -- 3 Maccabees : an anti-Dionysian polemic / Noah Hacham -- Third Maccabees : historical fictions and the shaping of Jewish identity in the Hellenistic period / Sara R. Johnson -- Humor and paradox in the characterization of Abraham in the Testament of Abraham / Jared W. Ludlow -- Resurrection and social perspectives in the apocryphal Acts of Peter and Acts of John / Judith B. Perkins -- The breasts of Hecuba and those of the daughters of Jerusalem : Luke's transvaluation of a famous Iliadic scene / Dennis R. MacDonand -- The choral crowds in the tragedy according to St. Matthew / J.R.C. Cousland -- The summaries of Acts 2, 4, and 5 and utopian literary traditions / Ruben Rene Dupertuis -- A biography of a motif : the empty tomb in the Gospels, the Greek novels, and Shakespeare's Romeo and Juliet / Andy Reimer